A molecular portrait of microsatellite instability across multiple cancers - Isidro Cortes-Ciriano (Nature Portfolio, 2017)
Some cancers with DNA mismatch repair deficiency display microsatellite instability. Here the authors analyse twenty three cancer types at the exome and whole-genome level, and identify loci with recurrent microsatellite instability that could be used to identify patients who would benefit from immunotherapy.